Mengkomunikasi Visual Bisniskan UMKM dalam Menghadapi Persaingan Bisnis Online - Mellasanti Ayuwardani; Azzam Alhafhizd; Mirza Dzaki Kamal; Rafi Willy Febrian; Setiawan Wibowo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
To remain competitive in the dynamic marketplace, Micro, Small, and Medium Enterprises (MSMEs) must prioritize product aesthetics and branding. A common challenge faced by many MSMEs is the lack of visually appealing products and a weak brand identity, particularly in terms of logos. A compelling and distinctive logo can effectively differentiate a brand from its competitors, cultivate customer trust, and enhance brand recall. The project partner, Roti Bakar Mas Royy, an MSME that leverages e-commerce platforms such as Gojek and Shopee Food, exemplifies these challenges. The business's visual communication issues stem from inadequate e-commerce visuals and the absence of a logo to serve as a corporate identity. To address these shortcomings, the community service team designed product visuals and a logo that align with the MSME's identity.